Synthesis and conformational preferences of short analogues of antifreeze glycopeptides (AFGP) - Urbańczyk, Małgorzata; Jewgiński, Michał; Krzciuk-Gula, Joanna; Góra, Jerzy; Latajka, Rafał; Sewald, Norbert (Beilstein Journal of Organic Chemistry, 2019)
Antifreeze glycoproteins are a class of biological agents which enable living at temperatures below the freezing point of the body fluids. Antifreeze glycopeptides usually consist of repeating tripeptide unit (-Ala-Ala-Thr*-), glycosylated at the threonine side chain. However, on the microscopic level, the mechanism of action of these compounds remains unclear. As previous research has shown, antifreeze activity of antifreeze glycopeptides strongly relies on the overall conformation of the molecule as well an on the stereochemistry of amino acid residues. The desired monoglycosylated analogues with acetylated amino termini and the carboxy termini in form of N-methylamide have been synthesized. Conformational nuclear magnetic resonance (NMR) studies of the designed analogues have shown a strong influence of the stereochemistry of amino acid residues on the peptide chain stability, which could be connected to the antifreeze activity of these compounds. A better understanding of the mechanism of action of antifreeze glycopeptides would allow applying these materials, e.g., in food industry and biomedicine.
Keywords: antifreeze glycopeptides; conformational preferences; NMR; PP II; solid phase synthesis